You are on page 1of 3

Math 345

Handout #2

1. Show that the product of any two integers of the form 4k + 1 is again of this form 4k + 1, whereas the product of two integers of the form 4k + 3 is of the form 4k + 1. (1) Let a and b of the form 4k + 1; that is, a = 4m + 1 and b = 4n + 1, where m, n Z. Then ab = (4m + 1)(4n + 1) = 16mn + 4m + 4n + 1 = 4(4mn + m + n) + 1 is of the form 4k + 1, where k = 4mn + m + n Z. (2) Let a and b of the form 4k + 3; that is, a = 4m + 3 and b = 4n + 3, where m, n Z. Then ab = (4m+3)(4n+3) = 16mn+12m+12n+9 = 16mn+12m+12n+8+1 = 4(4mn+3m+3n+2)+1 is of the form 4k + 1, where k = 4mn + 3m + 3n + 2 Z. 2. Show that the product of any two integers of the form 6k + 5 is of the form 6k + 1. Let a and b of the form 6k + 5; that is, a = 6m + 5 and b = 6n + 5, where m, n Z. Then ab = (6m+5)(6n+5) = 36mn+30m+30n+25 = 36mn+30m+30n+24+1 = 6(6mn+5m+5n+4)+1 is of the form 6k + 1, where k = 6mn + 5m + 5n + 4 Z. 3. Use the Division Algorithm to establish the following: (a) The square of any integer is either of the form 4k or 4k + 1. Let a Z. By the Division Algorithm, a is of the form 2k or 2k + 1. Case (1). a = 2k. Then a2 = 4k 2 . Thus a2 = 4q, where q = k 2 Z. Case (2). a = 2k+1. Then a2 = 4k 2 +4k+1 = 4(k 2 +k)+1. Thus a2 = 4q+1, where q = k 2 +k Z. (b) The cube of any integer has one of the forms: 9k, 9k + 1 or 9k + 8. Let a Z. By the Division Algorithm, a is of the form 3k, 3k + 1, or 3k + 2. Case (1). a = 3k. Then a3 = 9(3k 3 ). Thus a = 9q, where q = 3k 3 Z. Case (2). a = 3k + 1. Then a3 = 27k 3 + 27k 2 + 9k + 1 = 9(3k 3 + 3k 2 + k) + 1. Thus a = 9q + 1, where q = 3k 3 + 3k 2 + k Z. Case (3). a = 3k + 2. Then a3 = 27k 3 + 54k 2 + 36k + 8 = 9(3k 3 + 6k 2 + 4k) + 8. Thus a = 9q + 8, where q = 3k 3 + 6k 2 + 4k mathbbZ. (c) The fourth power of any integer is either of the form 16K + 1. Let a Z. By the Division Algorithm, a is of the form 4k, 4k + 1, 4k + 2, or 4k + 3. Case (1). a = 4k. Then a4 = 44 k 4 = 16(16k 4 ). Thus a = 16q, where q = 16k 4 Z. Case (2). a = 4k + 1. Then a4 = 256k 4 + 256k 3 + 96k 2 + 16k + 1 = 16(16k 4 + 16k 3 + 6k 2 + k) + 1. Thus a = 16q + 1, where q = 16k 4 + 16k 3 + 6k 2 + k Z. Case (3). a = 4k +2. Then a4 = 256k 4 +512k 3 +384k 2 +32k +16 = 16(16k 4 +32k 3 +24k 2 +2k +1). Thus a = 16q, where q = 16k 4 + 32k 3 + 24k 2 + 2k + 1 Z. Case (4). a = 4k+3. Then a4 = 256k 4 +768k 3 +864k 2 +432k+81 = 256k 4 +768k 3 +864k 2 +432k+ 80+116(16k 4 +48k 3 +54k 2 +27k+5)+1. Thus a = 16q+1, where q = 16k 4 +48k 3 +54k 2 +27k+5 Z. 4. Show that the product of any three consecutive integers is divisible by 6. Let a Z. By the Division Algorithm, a is of the form 6k, 6k + 1, 6k + 2, 6k + 3, 6k + 4, or 6k + 5. We will show below that in each case 6 divides a(a + 1)(a + 2). Case (1). a = 6k. Then a(a + 1)(a + 2) = 6k(6k + 1)(6k + 2) = 6(k(6k + 1)(6k + 2)) = 6q, where q = k(6k + 1)(6k + 2) Z. Thus 6 divides a(a + 1)(a + 2). Case (2). a = 6k + 1. Then a(a + 1)(a + 2) = (6k + 1)(6k + 2)(6k + 3) = (6k + 1)2(3k + 1)3(2k + 1)6(6k + 1)(3k + 1)(2k + 1) = 6q, where q = (6k + 1)(3k + 1)(2k + 1) Z. Thus 6 divides a(a + 1)(a + 2). Case (3). a = 6k + 2. Then a(a + 1)(a + 2) = (6k + 2)(6k + 3)(6k + 4) = 2(3k + 1)3(2k + 1)(6k + 4) =

6(3k+1)(2k+1)(6k+4) = 6q, where q = (3k+1)(2k+1)(6k+4) Z. Thus 6 divides a(a+1)(a+2). Case (4). a = 6k + 3. Then a(a + 1)(a + 2) = (6k + 3)(6k + 4)(6k + 5) = 3(2k + 1)2(3k + 2)(6k + 5) = 6(2k+1)(3k+2)(6k+5) = 6q, where q = (2k+1)(3k+2)(6k+5) Z. Thus 6 divides a(a+1)(a+2). Case (5). a = 6k + 4. Then a(a + 1)(a + 2) = (6k + 4)(6k + 5)(6k + 6) = (6k + 4)(6k + 5)6(k + 1) = 6(6k + 4)(6k + 5)(k + 1) = 6q, where q = (6k + 4)(6k + 5)(k + 1) Z. Thus 6 divides a(a + 1)(a + 2). Case (5). a = 6k + 5. Then a(a + 1)(a + 2) = (6k + 5)(6k + 6)(6k + 7) = (6k + 5)6(k + 1)(6k + 7) = 6(6k + 5)(k + 1)(6k + 7) = 6q, where q = (6k + 5)(k + 1)(6k + 7) Z. Thus 6 divides a(a + 1)(a + 2).

5. Show that if a is an integer, then 3 divides a3 a. Let a Z. Then a3 a = a(a2 1) = a(a + 1)(a 1) = (a 1)a(a + 1) = a3 a = (a 1)a(a + 1). Now (a 1)a(a + 1) is a product of three consecutive integers a 1, a, a + 1 and by the previous problem, 6 divides (a-1) a (a+1). Now 3|6 and 6|(a 1)a(a + 1). Thus, by Theorem 2.2 (d): If a|b and b|c, then a|c, 3|(a 1)a(a + 1). Hence, 3 divides a3 a. 6. Show that if a and b are integers such that a|b, then ak divides bk for every positive integer k. Given: a|b and k is a positive integer. Prove: ak |bk . Proof: Now a|b (given) = c Z such that b = ac (divisibility). Then bk = (ac)k . So bk = ak ck . Then ak |bk , since ck Z. 7. Let n Z. Prove that n is an even integer if, and only if, n = 2m with m Z. n is an even integer 2 divides n (denition) q Z such that n = 2q (divisibility). 8. Let n Z. Prove that n is an odd integer if, and only if, n = 2m + 1 with m Z. n is an odd integer 2 does not divides n (denition) q Z such that n = 2q + 1 (Division Algorithm). 9. Show that the sum of two even or of two odd integers is even, whereas the sum of an odd and an even integer is odd. (1) Let a and b be even integers. Then, by the previous problem, exists m, n Z such that a = 2m and b = 2n. Then a + b = 2m + 2n = 2(m + n). Now a + b = 2(m + n) and m + n Z. So a + b is even (see Problem 7 above). (2) Let a and b be odd integers. Then, by the previous problem, exists m, n Z such that a = 2m+1 and b = 2n+1. Then a+b = (2m+1)+(2n+1) = 2(m+n+1). Now a+b = 2(m+n+1) and m + n + 1 Z. So a + b is even (see Problem 7 above). (3) Let a and b be integers. Assume a is even and b is odd. Then, by the previous problem, exists m, n Z such that a = 2m and b = 2n + 1. Then a + b = 2m + (2n + 1) = 2(m + n) + 1. Now a + b = 2(m + n) + 1 and m + n Z. So a + b is odd (see Problem 8 above). 10. Prove that the product of two odd integers is odd, whereas the product of two integers is even, if either of the integers is even. (1)Let a and b be odd integers. Then, Problem above, exists m, n Z such that a = 2m + 1 and b = 2n + 1. Then ab = (2m + 1)(2n + 1) = 4mn + 2n + 2m + 1 = 2(2mm + m + n) + 1. Now ab = 2(2mn + m + n) + 1 and 2mn + m + n Z. So a + b is even (see Problem 8 above). (2) Let a and b be integers. Assume a is even. Then, Problem above, exists n Z such that a = 2n. Then ab = (2n)b = 2(nb). Now ab = 2(nb) and nb Z. So ab is even (see Problem 7 above).

11. Show that if a and b are positive integers and a divides b, then a b. Given: a and b are positive integers and a|b. Prove: a b. Proof: By Theorem 2.2 (f) : If a|b and b = 0, then |a| |b|, we have |a| |b|. Since a and b are positive, |a| = a and |b| = b. Hence a b. 12. Are there integers a, b, and c such that a divides bc, but a does not divide b and a does not divide c. Yes, for example, let a = 4, b = 6, and c = 2. Then a|bc (since 4|12). But a does not divide b (since 4 does not divide 6) and a does not divide c (since 4 does not divide 2). 13. What can you conclude if a and b are nonzero integers such that a divides b and b divides a? Now, By Theorem 2.2 (e), a|b and b|a if and only if a = b. Thus a = b. 14. If a, b, c, and d are integers with a and c nonzero, such that a | b and c | d, then prove that ac | bd. Given: a | b and c | d Prove: ac | bd Proof: Now a | b (given) = e Z such that b = ae and c | d (given) = f Z such that d = cf . Multiplying b = ae and d = cf , we have bd = aecf . Hence bd = ac(ef ) and ac|bd since ef Z. 15. If a, b, and c = 0 are integers, then a | b if and only if ac | bc. (=) Given: a | b and c = 0 Z. Prove: ac | bc. Proof: a | b (given) = d Z such that b = ad (divisibility). Multiply both sides of b = ad by c. Thus bc = adc. So ac(d) = bc. Since d Z, ac|bc (divisibility). (=) Given: ac | bc and c = 0 Z. Prove: a | b. Proof: ac | bc (given) = d Z such that bc = acd (divisibility). Since c = 0, we divide both sides of bc = acd by c. Thus b = ad and a|b since d Z.